PERSONAL SELF-DEVELOPMENT IN THE CONTEXT OF GLOBAL EDUCATION: THE TRANSFORMATION OF VALUES AND IDENTITY - Kassymova G. K.; Arpentieva M. R; Yurkova M. G.; Zhdanko T. A.; Gerasimova J. R.; Kravtsov A. Yu.; Egorova J. V.; Gasanova R. R.; Larionova L. A. (Scientific Journal of Pedagogy and Economics, 2019)
The article discusses the issues of pedagogical support for personal self-development and the problems of human self-development, acting as one of the leading trends in improving education and training in the context of globalization of the modern world and modern education. It considers the limitations and opportunities (pedagogical resources) of additional and global education in the field of personal self-development and the implementation of pedagogical ideas of Russian and foreign scientists. Global education is a complex idea that helps a person better understand the world. Thanks to global education, a person can comprehend the problems of relations between peoples and other social groups, the problems of war and migration, the problems of corruption and social justice, the problems of poverty and homelessness, the bioethical and biotechnological problems of mankind, the problems of ecology and culture, science and art, the problems of gender relations and generations, career and professional issues, science and education, other global aspects. He can comprehend them in the context of international representations. In addition, he can touch the “timeless” Vedic knowledge of his ancestors about the unity of the universe, its laws, etc. This can be done both through contact with the Vedic sources and texts proper, and in the context of understanding the ideas of modern cosmic scientists. Global (as Vedic) education is able to transform the way people understand themselves and the world, it helps them (trans) to shape themselves and the world in the most harmonious, authentic and congruent way. This will naturally manifest itself in the transformation of values and identities of pupils and students facilitate the proactive participation of people and their mutual learning and upbringing in the process of solving significant problems for their community and the context of the evolution of humankind, preventing and blocking involutionary processes.